2015
DOI: 10.1038/nm.3826
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMPKα2 in adipocytes is essential for nicotine-induced insulin resistance in vivo

Abstract: Cigarette smoking promotes body weight reduction in humans while paradoxically also promoting insulin resistance (IR) and hyperinsulinemia. The mechanisms behind these effects of smoking are unclear. Here, we show that nicotine, a major constitute of cigarette smoke, selectively activates AMP-activated protein kinase α2 (AMPKα2) in adipocytes, which, in turn, phosphorylates MAP kinase phosphatase-1 (MKP1) at serine 334, initiating a proteasome-dependent degradation of this latter protein. The nicotine-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
105
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(115 citation statements)
references
References 67 publications
10
105
0
Order By: Relevance
“…Numerous lines of evidence in models of diabetes, cardiovascular dysfunction, and obesity confirm the role of p38 as a possible mediator of IGFs/insulin resistance induced by oxidative stress (37)(38)(39)(40)(41)(42) and the potential benefits of its inhibition (43,44). p38 redox activation prevents IRS-1/2 phosphorylation by IGF-I or insulin, blocking in this way PI3K and AKT activation (45).…”
Section: Discussionmentioning
confidence: 92%
“…Numerous lines of evidence in models of diabetes, cardiovascular dysfunction, and obesity confirm the role of p38 as a possible mediator of IGFs/insulin resistance induced by oxidative stress (37)(38)(39)(40)(41)(42) and the potential benefits of its inhibition (43,44). p38 redox activation prevents IRS-1/2 phosphorylation by IGF-I or insulin, blocking in this way PI3K and AKT activation (45).…”
Section: Discussionmentioning
confidence: 92%
“…25 Nicotine can also increase insulin resistance by activation of adenosine monophosphateactivated protein kinase. 26 In the present study, cigarette smokers showed a trend to have higher waist circumference. Previous studies have reported inconsistent results on the relationship between smoking and waist circumference.…”
Section: Discussionsupporting
confidence: 53%
“…The rationale for using twice daily IP administration of nicotine (0.75 mg/kg BW) was based on the results of our previous studies, which demonstrated that this dose level of nicotine, when combined with HFD, triggered greater oxidative stress, activated hepatocellular apoptosis, amplified HFD-induced hepatic steatosis (Friedman et al 2012) and caused intramyocellular lipid accumulation and intramyofibrillar mitochondrial abnormalities in the skeletal muscle (Sinha-Hikim et al 2014). Notably, the daily dosage of 1.5 mg/kg BW in mice appeared to be similar to the clinically relevant concentrations found in habitual cigarette smokers and users of nicotine-containing chewing gum (Wu et al 2015). An additional group of five nicotine-treated mice on HFD received twice-daily IP injections of mecamylamine (1 mg/kg BW), a non-selective nicotinic acetylcholine receptor (nAChR) antagonist, for 16 weeks (Bacher et al 2009).…”
Section: Methodssupporting
confidence: 58%